2021
DOI: 10.1002/adfm.202107484
|View full text |Cite
|
Sign up to set email alerts
|

3D Wearable Fabric‐Based Micro‐Supercapacitors with Ultra‐High Areal Capacitance

Abstract: Miniaturized electronics require integrated unit configuration in very limited space, where energy storage per unit area is thus extremely critical. Micro-supercapacitors (MSCs), mainly established on planar substrates, are superior but still suffer from limited areal capacitance. Herein, a novel strategy is introduced to construct high cross-section MSCs using 3D fabrics as the porous skeleton. Interdigitated poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) is patterned on 3D fabrics to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…The device showed excellent durability, with no changes in the cyclic voltammetry (CV) curve before and after washing. Furthermore, the 3D fabric-based supercapacitor exhibited a remarkable areal capacitance (~135.4 mF cm −2 ) 3.5 times higher than that of the planar substrate (PET) based supercapacitor (Figure 5h) [187].…”
Section: Fabric Shaped Durable E-textilesmentioning
confidence: 94%
See 1 more Smart Citation
“…The device showed excellent durability, with no changes in the cyclic voltammetry (CV) curve before and after washing. Furthermore, the 3D fabric-based supercapacitor exhibited a remarkable areal capacitance (~135.4 mF cm −2 ) 3.5 times higher than that of the planar substrate (PET) based supercapacitor (Figure 5h) [187].…”
Section: Fabric Shaped Durable E-textilesmentioning
confidence: 94%
“…(h) (i) Fabrication of 3D fabric-based micro supercapacitor, (ii) capacitance retention of the device over 3000 bending cycles, (iii) cyclic voltammetry curve of the supercapacitor before and after washing. Reproduced with permission [187] Copyright 2021, Wiley. Tian et al reported a wearable piezoresistive sensor from polyester (PET)/polyethylene (PE) fiber-based 3D nonwoven fabric coated with multi-walled carbon nanotubes (MWCNT).…”
Section: Fabric Shaped Durable E-textilesmentioning
confidence: 99%
“…It is essential to develop new energy technologies such as lithium (Li)-ion batteries (LIBs), supercapacitors, or solar cells with efficient energy storage and conversion ability to deal with the energy and environmental crisis. [1][2][3][4][5] However, as the traditional graphite anode Large specific surface area because of high structure porosity can reduce the local effective current density. Therefore, the use of 3D current collectors mainly prolongs the Sand's time and slows down the formation of Li dendrites by reducing the local effective current density.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to develop new energy technologies such as lithium (Li)‐ion batteries (LIBs), supercapacitors, or solar cells with efficient energy storage and conversion ability to deal with the energy and environmental crisis. [ 1–5 ] However, as the traditional graphite anode in LIBs, the low theoretical capacity can no longer meet the requirement of high‐density energy supply. [ 6–11 ] Therefore, it is of great significance to seek alternative Li anode materials to improve its specific capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies are needed to develop energy storage devices with a long lifespan, miniaturization, and flexibility. 9,10 Furthermore, implantable secondary energy storage devices that are safe for living cells but that do not interfere with biological functions can be used. 11…”
Section: Introductionmentioning
confidence: 99%